Discovery of isomiRs in PBMCs of diseased vis-à-vis healthy Indian water buffaloes - Jasdeep Kaur Dhanoa; Jasdeep Singh; Amarjit Singh; Jaspreet Singh Arora; R. S. Sethi; C. S. Mukhopadhyay (ExRNA, 2019)
Abstract Background MicroRNA isoforms are the variants of a canonical miRNA-sequence with alteration at the 3` or 5` termini due to addition, deletion and/or substitution of nucleotide. The present study aims at identifying the isomiRs of the expressed miRNAs in peripheral blood mononuclear cells (PBMCs) of diseased vis-à-vis healthy buffaloes, vis-à-vis exploring the molecular pathways of the predicted target genes of the isomiRs/miRNAs. Four groups of experimental animals (adult, male or female) were included in the study: a) Brucellosis (Murrah breed), b) Paratuberculosis or Johne’s disease (Murrah breed); c) Brucellosis (Nili-Ravi breed) and d) control group of healthy buffaloes of the Murrah breed. The small RNA (sRNA) samples, extracted from PBMCs of each of the four groups, pooled into four samples and then were subjected to next-generation sequencing (Ion-Torrent PGM™ platform). Results The NGS data were analyzed using the miRanalyzer tool and R-programming to identify the differentially expressed (up and down-regulated (fold change ratio > 2)) miRNAs (exhibiting isomiRs and uniquely expressed miRNAs having isomiRs) of each of the three disease-groups as compared to the healthy-Murrah group. The target genes of these selected differentially and uniquely expressed miRNA & isomiRs were predicted using three different online tools (TargetScan, PicTar, and miRDB). These target genes were analyzed to determine their role in systems biology. We identified 153, 125 and 139 isomiR-exhibiting miRNAs that were common in those three experimental groups (healthy vs. Brucellosis-Murrah, Johne’s disease-Murrah, and Brucellosis-Nili-Ravi, respectively). Gene ontology and pathway analyses of the target genes (Panther classification system) yielded several biological hits. Functional classification of the target genes indicated that these target genes were involved in different systems biology related functions like molecular binding, enzyme modulation, signal modulation, etc. The specificity of function was varying in the three experimental groups. Conclusion We are presenting the first report on the identification of isomiRs and functional classification of the target genes in water buffaloes. The results revealed that isomiRs may be involved in the biological processes and can be used in disease diagnosis.